Peran Orangtua dalam Meningkatkan Hasil Belajar Siswa Pada Mata Pelajaran Bahasa Indonesia di Kelas IV SDN 1 Sukarara: The Role of Parents in Improving Student Learning Outcomes in Indonesian Language Subjects in Grade IV of SDN 1 Sukarara - Husnul Laili (Pendidikan Al-Gafari, 2025)
Parents are the main responsible for their children's education. Wherever the children are educated, whether in formal, informal, or non-formal institutions, parents still play an active role in determining their children's future. Education outside the family does not mean releasing parental responsibility in children's education. Still, it is done by parents solely because of the limited knowledge possessed by parents, because of the nature of knowledge that continues to develop following the times, while parents have limitations. The purpose of this study was to determine the role of parents in improving student learning outcomes in the Indonesian Language subject at SDN 1 Sukarara. This study is a qualitative descriptive study, which took place at SDN 1 Sukarara. Resource center. The techniques used in data collection are observation, interviews, and documentation. The data collection techniques used are reduction, data display, and conclusion drawing. The results of research data on the role of parents in improving student learning outcomes in the Indonesian Language subject are that parents act as role models, reflections of children, and facilitators. Based on the data analysis conducted at SDN 1 Sukarara, it can be concluded and understood that every child, when they come home from school, must control and pay attention to their lessons so that children are more active in lessons and can improve student learning outcomes. There are parents whose roles are lacking because they are busy with work.